Inteligencia Artificial (de)generativa: Sobre la imposibilidad de que un sistema de IA tenga una experiencia moral = (De)generative Artificial Intelligence : On the Impossibility of an AI System having a Moral Experience - Serafim, Mauricio-C. (Scripta theologica, 2024)
Artificial Intelligence (AI) raises ethical concerns. This article discusses the Ethics of AI, focusing on artificial moral agency (AMA), with the purpose of investigating whether AI can possess moral agency similar to human beings, or more precisely, have a moral experience. We argue that AI lacks the intrinsic capacity provided by freedom for moral agency. By employing cybernetic approaches and systems theory, we conclude that AI emulates ‘principles of judgment’ by adhering to extrinsic norms, highlighting the need for reflection on AMA and its social impacts.